“ Usṭūrat Al-Jabal ”: The Politics of Space in Hussein Barghouti’s Among the Almond Trees - Shatha Abd El Latif; Lujain Aqra; Bilal Hamamra (Arab Studies Quarterly)
Drawing on Derrida’s concept of hauntology, Edensor’s notions of spatial memory, and Maddern and Adey’s spectro-geographies, this article scrutinizes the intricate politics of space in Hussein Barghouti’s memoir Among the Almond Trees , focusing on the symbolic and spatial significance of the monastery in Kobar. Barghouti employs the ruins of the monastery as a conduit for ancestral memories that disrupt colonial spatiotemporal narratives and invoke a spectral presence that defies linear temporality. The memoir weaves together the material and the mystical, portraying the landscape as an active participant in the textual space. We contend that the memoir is a site of ecological and anti-colonial resistance, where the land’s fauna and flora serve as a counter-narrative to the Israeli colonial project which seeks to transform and dominate the Palestinian landscape.